2016
DOI: 10.21839/jaar.2016.v1i3.29
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation of conventional diets commonly fed to dairy cows in Central Myanmar

Abstract: This study consisted of two experiments conducted to evaluate the effective net gas, fermentation kinetics (experiment 1), methane gas concentration, partitioning factor (PF) for microbial protein synthesis and in vitro dry matter digestibility (IVDMD) (experiment 2) of conventional diets commonly fed to dairy cows in Central Myanmar. The conventional diets from four areas [diet from Sin Tel area (Diet-ST), diet from Myay Nguarea (Diet-MN), diet from Ta Pelarea (Diet-TP) and diet from Amarapuraarea (Diet-AM)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Hemicellulose is hydrolyzed by rumen microbes and hemicellulase enzyme, whose final fermentation product is VFA (Liu et al 2020). The DMD and OMD values of feed ingredients in the present study have exceeded those of agricultural by-product feedstuffs already tested (Aung et al 2015).…”
Section: Dry Matter and Organic Matter Digestibility Rdp And Rupcontrasting
confidence: 54%
“…Hemicellulose is hydrolyzed by rumen microbes and hemicellulase enzyme, whose final fermentation product is VFA (Liu et al 2020). The DMD and OMD values of feed ingredients in the present study have exceeded those of agricultural by-product feedstuffs already tested (Aung et al 2015).…”
Section: Dry Matter and Organic Matter Digestibility Rdp And Rupcontrasting
confidence: 54%
“…Moreover, Ngwe et al (2012) and Fuma et al (2012) suggested that bean husk supplementation, especially lablab bean husk, might improve the nutritive value of rice straw diet by stimulating fibrolytic bacteria and other associated bacteria. Another reason for the variation of feed intake for dairy cows was the partitioning factor (PF) for the microbial protein synthesis (MPS) efficiency which was highest in Diet-MN (Aung et al, 2016). Blummel et al (1999) recommended that roughage with higher PF has been shown to have higher DMI.…”
Section: Discussionmentioning
confidence: 99%
“…According to the report of Aung et al (2016), it was noted that the lowest partitioning factor (PF) for microbial protein synthesis (MPS) efficiency was also found in Diet-AM among the experimental diets. Not only digestibility of DM but also that of CP was correlated with the efficiency of microbes in the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations